The FAST-M Complex Intervention for the Detection and Management of Maternal Sepsis in Low-resource Settings: A Multi-site Evaluation. Issue 2 (24th June 2022) - Cheshire, J.; Jones, L.; Munthali, L.; Kamphinga, C.; Liyaya, H.; Phiri, T.; Parry-Smith, W.; Dunlop, C.; Makwenda, C.; Devall, A.J.; Tobias, A.; Nambiar, B.; et al.
Abstract : ( BJOG . 2021;128:1324–1333) Maternal sepsis is the third most common direct cause of maternal mortality worldwide. Low-resource settings are disproportionately affected by maternal sepsis. While sepsis screening and care bundles can reduce the time to initiation of treatment and improve outcomes, the current bundles are not specific to maternal care nor are they suitable for low-resource settings. The FAST-M maternal sepsis care bundle was developed using a modified Delphi process with input from care providers from low- to middle-income countries. This study aimed to gauge the feasibility of implementing the FAST-M complex intervention in low-resource settings.